2020
DOI: 10.20965/jdr.2020.p0324
|View full text |Cite
|
Sign up to set email alerts
|

Projecting the Impact of Climate Change on Temperature, Precipitation, and Discharge in the Bago River Basin

Abstract: Climate change affects both the temperature and precipitation, leading to changes in river runoff. The Bago River basin is one of the most important agricultural regions in the Ayeyarwady Delta of Myanmar, and this paper aims to evaluate the impact of climate change on it. Linear scaling was used as the bias-correction method for ten general circulation models (GCMs) participating in the fifth phase of the Coupled Model Intercomparison Project. Future climate scenarios are predicted for three 27-year periods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It is located between 18 • 8 ′ and 19 • 20 ′ N and 95 • 50 ′ and 96 • 45 ′ E (see Figure 1) in the central part of Myanmar. The minimum temperature is 21 • C, and the maximum temperature is 32 • C [22]. The average annual precipitation ranges between 2500 mm and 3000 mm [21].…”
Section: Study Sitementioning
confidence: 99%
“…It is located between 18 • 8 ′ and 19 • 20 ′ N and 95 • 50 ′ and 96 • 45 ′ E (see Figure 1) in the central part of Myanmar. The minimum temperature is 21 • C, and the maximum temperature is 32 • C [22]. The average annual precipitation ranges between 2500 mm and 3000 mm [21].…”
Section: Study Sitementioning
confidence: 99%
“…They evaluated 22 models under the CMIP5 and found the models to have a comparatively lower skill over East Africa while Fotso-Nguemo et al [27] found RCP8.5 to present rainfall magnitudes comparatively lower than the Global Precipitation Climatology Center (GPCC) and Tropical Rainfall Measuring Mission (TRMM). While using RCP4.5 and RCP8.5 and 10 GCMs along with linear scaling as the bias correction method, Myo et al [18] found that these RCPs projected fluctuating average monthly precipitation but found that annual precipitation is likely going to increase. These results are consistent with our findings which make us conclude that the 21 st century precipitation is going to be highly variable at monthly scale.…”
Section: The Temporal Performance Of the Wrf Model For The Different Rcpsmentioning
confidence: 99%
“…linear scaling, gamma quantile mapping, generalized quantile mapping, and power transformation and noted that the power transformation method was the most suitable for bias correction of the GCM. However, Myo et al [18] and Ghimire et al [15] found the linear scaling method to produce the best performance and recommended it for hydrological studies at river basins. On the other hand, Mahmood & Mukand [19], and Sharma & Kumar [14] recommended the quantile mapping bias correction method.…”
Section: Introductionmentioning
confidence: 99%
“…However, When the scenarios of RCP4.5 and RCP8. 5 were applied in 10 GCM bias correction methods by applying linear scale, Miao et al [33] showed the RCP projected inconsistent mean values in monthly terms but annual ones was likely to rise. Our results support the findings that the future will be more fluctuated at monthly temporal scale.…”
mentioning
confidence: 99%